Digital-Based Self-Employed Tendencies in Maintaining Income Levels in the Red Zone of COVID-19 - Efriyani Sumastuti; Dhea Rizky Amelia; Ika Indriasari; Rita Meiriyanti (PT Mattawang Mediatama Solution, 2023)
This study has two objectives: wanting to know the tendency of Self-Employed in the COVID-19 red zone to maintain income levels and the predictive probability of using digitalization to maintain income levels in the COVID-19 Pandemic Era. Secondly, wanting to know the socio-demographic factors of Self-Employed in the red zone and have used a digital approach in their work to maintain income levels during the COVID-19 pandemic. Data sourced from Sakernas August 2020, with logistic regression analysis method. Self-Employed in the red zone of COVID-19 have a lower tendency than those who work in the green zone of COVID-19 to maintain their income level. On the other hand, Self-Employed who have been digitized have a greater probability of increasing their income. Furthermore, Self-Employed with a digital approach who do not work in crowds, do not experience a decrease in working hours, have high skills, and live in villages have a greater probability of maintaining income levels in the red zone of COVID-19.